2015
DOI: 10.1109/tlt.2015.2416717
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Student Motivation by Using a QR-Based U-Learning Material Production System to Create Authentic Learning Experiences

Abstract: This study developed a QR-based U-Learning Material Production System (QR-ULMPS) that provides teachers with an education tool to motivate college level students enrolled in a liberal arts course. QR-ULMPS was specifically designed to support the development of u-learning materials and create an engaging context-aware u-learning environment for students. A quasi-experimental research design was used to evaluate the overall effectiveness of QR-ULMPS; the Unified Theory of Acceptance and Use of Technology (UTAUT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 29 publications
(43 reference statements)
2
11
0
7
Order By: Relevance
“…As for the confidence dimension, students in the experimental group reported higher levels than those using the traditional learning materials. This result is in agreement with other studies that have demonstrated that AR applications are useful for supporting the confidence dimension of motivation (Chen et al, 2016;Chiang et al, 2014;Chin et al, 2015), and may suggest that students perceived that they can succeed in the learning activities and that they have greater control over their learning process. This result might be explained by the fact that the components of the framework implemented in the AR applications allowed students to learn at their own pace and allowed them, in this particular learning domain of chemistry, to explore multiple possibilities for solving problems and obtain automatic feedback, which is something that is not possible to achieve directly with traditional learning materials.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As for the confidence dimension, students in the experimental group reported higher levels than those using the traditional learning materials. This result is in agreement with other studies that have demonstrated that AR applications are useful for supporting the confidence dimension of motivation (Chen et al, 2016;Chiang et al, 2014;Chin et al, 2015), and may suggest that students perceived that they can succeed in the learning activities and that they have greater control over their learning process. This result might be explained by the fact that the components of the framework implemented in the AR applications allowed students to learn at their own pace and allowed them, in this particular learning domain of chemistry, to explore multiple possibilities for solving problems and obtain automatic feedback, which is something that is not possible to achieve directly with traditional learning materials.…”
Section: Discussionsupporting
confidence: 92%
“…This might suggest that the learning experience based on our framework captured student interest, created curiosity and helped students to focus on the key information of the learning content. This result supports previous studies reporting the positive impact AR applications have on the attention dimension (Chen et al, 2016;Chiang et al, 2014;Chin et al, 2015;Ibanez et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Student response to learning implementation consists of components, among others: (1). Compliance of the lecture with the lesson plan (learning implementation plan); (2) Discipline of lecturer on time of college; (3) The ability of lecturers in the presentation of lecture materials; (4) The ability of lecturers to motivate students; (5) The ability of lecturer improvisation; (6) Interaction of lecturers and students; (7) Conformity of exam with course material; (8) Lecturer's service to students; (9) The use of teaching aids by lecturers and (10) Mastery of material by lecturers [5]- [6]- [7]- [8]. The determinant factors that are not less important to the above are the degree of student satisfaction with facilities and utilization of institutional resources [9]- [10]- [11].…”
Section: Introductionmentioning
confidence: 99%
“…Because of that, achievement motivation is importance to be empowered in the learning process of vocational education for involve the student directly in the learning process so the student performance becomes maximal (Purwaningsih & Suwarno, 2016;Ergül & Kargın, 2014). Achievement motivation will encourage the student to always work hard in maintaining and improving their best achievement and to be afraid of failure (Chin, Lee, & Chen, 2015;Litzinger, Lee, Wise, & Felder, 2007).…”
Section: Introductionmentioning
confidence: 99%